Collisions of Nucleons with Atoms: Calculated Cross Sections and Monte Carlo Simulation - Salvat, Francesc; Quesada, José Manuel (Frontiers in Physics, 2021)
After a summary description of the theory of elastic collisions of nucleons with atoms, we present the calculation of a generic database of differential and integrated cross sections for the simulation of multiple elastic collisions of protons and neutrons with kinetic energies larger than 100 keV. The relativistic plane-wave Born approximation, with binding and Coulomb-deflection corrections, has been used to calculate a database of proton-impact ionization of K-shell and L-, M-, and N-subshells of neutral atoms These databases cover the whole energy range of interest for all the elements in the periodic system, from hydrogen to einsteinium ( Z = 1 –99); they are provided as part of the PENH distribution package. The Monte Carlo code system PENH for the simulation of coupled electron-photon-proton transport is extended to account for the effect of the transport of neutrons (released in proton-induced nuclear reactions) in calculations of dose distributions from proton beams. A simplified description of neutron transport, in which neutron-induced nuclear reactions are described as a fractionally absorbing process, is shown to give simulated depth-dose distributions in good agreement with those generated by the G EANT 4 code. The proton-impact ionization database, combined with the description of atomic relaxation data and electron transport in PENELOPE , allows the simulation of proton-induced x-ray emission spectra from targets with complex geometries.